Peran Orangtua Dalam Menanamkan Nilai-Nilai Islam pada Anak di Era Digital - Arlina; Siregar, Evi Rizky Sari; Hasibuan, Fadila; Ramadhani, Fathis Silmi; Sitepu, M. Fadliq Ananta (Ikatan Dai Indonesia, 2023)
This study aims to explain the role of parents in instilling Islamic values in children in the digital era which includes Islamic education, worship, morals, rewards and punishments to children in the digital era. This type of research is qualitative descriptive research. The data sources in this study are the people closest to the writer who are in Medan City. Data collection techniques used in this study were observation and interviews. Data analysis techniques used are data editing, data presentation, and conclusion drawing. The results obtained show that 1) the role of parents in instilling Islamic education by teaching prayers, stories of the Prophet, the message of Allah, and introducing hijaiyah letters, 2) The role of parents in worship by getting used to, practicing, motivating, and advising children, and with affection, 3) The role of parents in instilling morals by exemplifying and showing the story of the morals of the Prophet Muhammad so that children can imitate them in their lives, 4) Giving rewards and punishments in moderation and still within Islamic guidelines.